Anatomical Study of Triangle of Brocq and Mouchet in Human Cadaveric Heart - Kharbuja, Rabita; Basnet, LM; Dhungel, S (Nepal Medical College Journal, 2020)
Right and left coronary arteries maintain the nutritional supply of heart. The left coronary artery (LCA) bifurcates into Anterior Interventricular Artery (AIA) and Circumflex Artery (CA). Triangle of Brocq and Mouchet is an arterio-venous triangle formed by AIA and CA of left coronary artery and great cardiac vein (GCV) that lies between conus aretriosus and left auricle. This study aims to determine frequency of Brocq and Mouchet triangle and its anatomical details. This study was conducted in thirty formalin fixed cadaveric hearts collectively available in the Department of Anatomy, Nepal Medical College from November 2019 till April 2020. The incidence of heart showing the triangle was 93.3% with the most common type being closed which is followed by inferiorly opened, superiorly opened, and completely opened. Most frequent content of the triangle was median artery followed by diagonal branches of AIA and CA. the mean area of the triangle was 218.84mm2(527.97 mm2-57.26 mm2). The branches of LCA varied from bifurcation to pentafurcation. Relationship of GCV with AIA and CA was found to be either superficial or deep. The anatomical knowledge of the Brocq and Mouchet triangle regarding arterio-venous relationship will be required for angiographic procedures. Also, the triangle is a potential epicardial access route to mitral valve annulus thus detailed anatomical knowledge of the triangle will help cardiologist to achieve successful cardiological procedures with minimal complications.